A Review of Comparative Study on Solid Waste Management Practices in Four Different Cities in Asian Countries - Adhikari, Bikash; Paudel, Samikshya (Kathmandu University Journal of Science, Engineering and Technology, 2020)
Waste management is a grassroots level problem, and a decentralized and interdisciplinary approach is required to solve this problem. The exponentially growing population and the fast-changing socio-cultural behaviors of humans influencing mass production and consumption rates are not environmentally sustainable, and this explicitly defines the big picture in the solid waste management scenario. The emerging threat to the world is not only the alarming growth in the production of waste but also the unabating mismanagement of the waste we produce. This menace is troubling urban areas of both the developing and the developed nations with high population densities as waste management is often practiced as putting wastes away from immediate sight. After reviewing a few papers about the solid waste management practices around the world, it intrigued me to write how the best practices differ from the worst practices in waste management around Asian cities. In this paper, we assess solid waste management scenarios around four Asian cities and throw a light on the management practices that the best ones are doing differently to create a more sustainable urban environment for the residents. The countries that invest in a holistic evaluation of waste produced by their citizens and conduct proper research on how to manage wastes by utilizing locally available resources seem to perform better in the waste management sector.